Eight Integrations of Holistic Education Practices in Islamic Educational Institutions - Pratama, Achmad Galih; Aryanti, Yosi; Ridwan, Mohammad; Wahyudi, Fajar Satriyawan; Kohhar, Wildan Wafa Amrul; Rosyadi, Nabil (Khalifa: Journal of Islamic Education, 2024)
Holistic education aims to educate students comprehensively, both in terms of religious knowledge and general knowledge. However, in reality, holistic education in Islamic educational institutions such as Islamic boarding schools has not been implemented properly. Students must be equipped with various abilities or skills to live their lives and pursue their future careers. Therefore, this study aims to analyze the implementation of holistic education in Islamic educational institutions. This study uses a qualitative method with a case study approach. Data sources were obtained through in-depth interviews with twelve informants consisting of two school leaders, six senior and junior teachers, and three students. All informants were selected using snowball sampling. To support the interview data, the author also conducted direct observations for one month on how holistic education is practiced in the educational institutions under study. In addition, the author also analyzed academic documents that support data related to the research topic. All data were analyzed thematically using the interactive Miles and Huberman technique. The findings show that there are eight practices implemented in holistic education in Islamic educational institutions where this research was conducted. These eight practices are integrated into the teaching of religious beliefs and morals, general knowledge, public speaking skills training, social intelligence interaction, leadership basics, independence, discipline, and physical endurance. These findings can be used as a reference for educational institutions to implement true holistic education. Furthermore, the author suggests that future researchers conduct studies related to this issue, such as holistic education learning methods.